The Study of the Nerviano Lazaretto in the Context of the 17th-Century Plague - Fusco, Roberta; Vanni, Arianna (Medicina Historica, 2024)
The study of the Nerviano Lazaretto in the context of the 17th-century plague is essential for understanding the historical significance of epidemics. This site, with its unique combination of historical documents and human remains, offers an extraordinary opportunity to deepen our understanding of the plague's impact on the local population. A comprehensive interdisciplinary study integrating historical, anthropological, paleopathological, and archaeological data is necessary to unravel the complexities of the epidemic's effects. The findings from this research could not only enrich our understanding of the 17th-century plague but also contribute to the preservation of historical and anthropological heritage associated with the epidemic.